Prosmittia verae sp. n. – a new chironomid species (Diptera: Chironomidae: Orthocladiinae) from the environs of Sochi Town (the Northern Caucasus) - A.B. Krasheninnikov; E.A. Makarchenko (Кавказский энтомологический бюллетень, 2008)
The male imagines of Prosmittia verae sp. n., the new species from the environs of Sochi Town (the Northern Caucasus) are described and illustrated. The new species is separated from all known species of the genus by presence of the outer projection 7–8 µm long in the distal part of gonostylus. A key to males of the Prosmittia species of the Palaearctic region is provided